ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT. JAYA KUSUMA SARANA - Aditya Arya, Angga; Dharmayanti, G.A.P Candra; Parami Dewi, A.A Diah (JURNAL SPEKTRAN, 2018)
The rapid development of infrastructure in Bali has increased the number of service providers in construction field, one of them are contractors. A contractor must be able to demonstrate good performance to face the competition in construction field. The success of an enterprise is influenced by many sources in the company, including human resources, technology and money. Human resources have an important role to achieve the organization's objectives. PT. Sarana Jaya Kusuma (JKS) is one of the contractors that have obtained ISO 9001: 2008, and based on evaluation of the implementation of ISO 9001 in 2013, the quality of Human Resources at PT. JKS Bali still needs to be improved in accordance with indicators of objectives and targets of each division. Therefore this research aims to analyzed factors and dominant factors that  affect on the performance of employees. This research was conducted using quantitative methods. Data was collected through a survey using questionares and was analyzed using factor analysis to determine the factors and the dominant factors that affect the performance of employees at PT.JKS. The result suggested 13 factors that affect the performance of employees at PT. JKS, which was classified into 6 groups. The first group was training, interest and education; the second group was ability, discipline, evaluation; the third group was social security and perception of the rule; the fourth group was leadership and reward; the fifth group was work placement and the capacity of self; the sixth group was resource. The first group was the dominant factor than covered training, interest and education. Therefore, in order to improve their employee performance, PT. JKS should pay attention particularly to the dominant factors, i.e.: by providing training, identifying interest and education of the employees that suitable for their job description. Key Words : Employee performance, PT. Jaya Kusuma Sarana, ISO 9001